Insulin Degludec Versus Insulin Glargine on Glycemic Variability in Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yang, Yunjiao; Long, Cong; Li, Tongyi; Chen, Qiu (Frontiers in Endocrinology, 2022)
Background /Aims: Currently, glycemic variability has more deleterious effects than sustained hyperglycemia and is closely associated with acute and chronic complications of diabetes. Reducing glycemic excursion is becoming another vital goal of glycemic control in clinical practice. This study aimed to determine whether insulin degludec (IDeg) or insulin glargine (IGla) is more beneficial for reducing glycemic fluctuations. Materials and Methods: This research was constructed according to the PRISMA guidelines. We searched eight databases and ClinicalTrials.gov. from their inception to November 30, 2021. All randomized controlled trials comparing the efficacy of glucose variability between IDeg and IGla in diabetic patients were included. Results: Fourteen trials with 8683 participants were included. In patients with T1DM, IDeg was associated with a lower mean (MD: -16.25, 95%CI -29.02 to -3.07, P=0.01) and standard deviation (P=0.03) compared to IGla in fasting blood glucose (FBG); In people with T2DM, IDeg was related to a lower mean of FBG versus insulin glargine100U/mL (IGla100) (P<0.001) and had more extended time in range (TIR) than IGla100 (SMD:0.15, 95%CI 0.02 to 0.27, P=0.02) but not longer than insulin glargine 300U/mL (IGla300). Moreover, IDeg had a lower coefficient of variation of FBG than IGla (P=0.0254). For other indicators of glycemic variability, including standard deviation of blood glucose of 24h, mean of 24-h blood glucose, mean amplitude of glycemic excursion, coefficient of variation of 24h, mean of daily differences, area under the glucose curve, and M-value, no significant differences were identified between IDeg and IGla, regardless of T1DM or T2DM. Conclusions: Based on the current studies, there was comparable efficacy between IDeg and IGla from multiple aspects of glycemic variability, regardless of T1DM or T2DM. However, IDeg may be superior to IGla in reducing FBG variability in T1DM and T2DM. Nonetheless, due to the limitations of the original studies, it is still unclear whether IDeg is superior to both IGla100 and IGla300. In T2DM, IDeg had more extended TIR than IGla100 but not longer than IGla300. In addition, more well-designed randomized controlled trials comparing IDeg with IGla300 for different indicators of glycemic variability are still warranted.